Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

From $\displaystyle \frac{\log_n b}{\log_n a}$, how do we get $\log_a b$ using algebra?

I haven't been able to do it for about an hour now; I would love some help! Thanks!

share|cite|improve this question
up vote 7 down vote accepted

What you are looking at is the "change of base formula" for going from logarithms base $n$ to logarithms base $a$. I'm going to interpret your question as asking why the formula $$\frac{\log_nb}{\log_na} = \log_ab$$ is true.

To see why it is true, remember the meaning of the logarithms. Let's give these quantities names:

$$\log_n b = r,\qquad \log_n a = s,\qquad \log_a b = t.$$

That $\log_n b = r$ tells you that $n^r = b$. Similarly, $n^s = a$ (since $\log_n a = s$), and $a^t = b$ (because $\log_ab = t$).

So, $$n^r = b = a^t = (n^s)^t = n^{st}$$ which tells you that $n^r = n^{st}$. But that means that $r=st$. Now let's go back to the expressions for $r$, $s$, and $t$ using logarithms: $r=st$ is the same as $$\log_n b = \bigl( \log_n a\bigr)\bigl(\log_a b\bigr).$$ Now just solve for $\log_ab$.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.